ASRI SAADETİN İLK MÜEZZİNLERİ - Akbaş, Mehmet (Fırat University, 2014)
Resûlullah, Müslümanları namaza davet için ezan okunmasına karar verince bu iş için ilk önce Bilâl-i Habeşi’yi görevlendirdi. Daha sonra Kubâ Mescidi’nde bir başka sahâbîyi ezan okumakla görevlendirdi. Medine’de Bilâl’in yanı sıra müezzinlik yapan diğer bir sahâbî de Abdullah İbn Ümmi Mektûm oldu. Mekke’nin fethinden sonra da Kabe’ye müezzin olarak Ebû Mahzûre elCumahî tayin edildi. Bu çalışmada asr-ı saâdetin müezzinlerinin kimler olduklarını ve müezzinliklerinin nasıl başlayıp ne kadar devam ettiğini incelemeye çalışacağız

When the Prophet Mohammad decided on a’zan a special recitation that Muslims use to indicate it is time for praying to the call the Muslims for the prayer, he commissioned Bilâl for that post. After that, he commissioned another sahabe for the Quba Masjid. In Madina, beside Bilâl, another sahabe called Abdollah Ibn Ommu Maktoom was commissioned as well. After the conquest of Mecca, Abo Mahzoora was determined as the caller for pareyer in Kaba. In this study we will try to shed some light on who are these callers for prayer and to examine how they started to do these jobs and for how long they continued to fulfill these posts during the time of the Prophet
The First Callers for Prayer in the Period of the Prophet